Marketing Constraints to Goats in the Western Hill of Nepal - Nepali, Megh B.; Tiwari, Megh R.; Sapkota, Sudha; Poudel, Hari P.; Acharya, Budhi R.; Gautam, Sudeep (Nepal Agriculture Research Journal, 2014)
Goat marketing study was conducted in eleven districts with the objectives of exploration the existing goat marketing system in western hills of Nepal. The methodology of the study was households survey, Rapid Marketing Appraisal and use of secondary data. Some of the marketing centers are at the village level, catchments, terminal level markets and district headquarters. There are some marketing agents dealing with the goat marketing from village to the municipalities. Goat marketing agents mainly found farmers and middlemen at the village level and catchments markets. In terminal markets mainly wholesalers and middlemen were involved where as in district headquarters and municipalities middlemen, wholesalers and butchers were dealing the goat business. 59.3% respondents believed that middlemen visit in the village for goat marketing. Almost all farmers sell their goats on the basis of estimated price. Major constraints on goat marketing were lack of public goat marketing centres, lack of communications about goat marketing and lack of infrastructure etc in all the domestic markets. In the western hills of Nepal main goat marketing centre was found in Pokhara sub municipality where traders/whole sellers bring their goats to sale from different catchments. Government has the provision of establishing new goat marketing centers in each VDCs and district headquarters. Nepal Agric. Res. J. Vol. 8, 2007, pp. 95-102 DOI: http://dx.doi.org/10.3126/narj.v8i0.11601